Battle grounds: the female body as a site of war - Mironas, Alexandrina (My University, 2024)
On February 24, 2022, Russia escalated the ongoing Russo-Ukrainian war to a full-blown invasion of Ukraine. As a war tactic, Putin endorses gender-based violence by employing rape rhetoric to frame Ukraine as a powerless woman, and to demand the submissiveness that he believes is owed to him. To elucidate the socio-political forces behind gender-based violence as a war tactic, I reveal the relationship between traditional gender roles in Eastern Europe and how they establish the female body as the property of a nation. Through the examination of relevant literature, I draw a theoretical perspective that identifies the female body as nationalized, objectified as property, and inscribed as a site of violence. Applying this lens to the invasion of Ukraine, I identify the social and political forces that allow Russian soldiers to objectify the Ukrainian female body as a battle ground on which national wars are fought. Further, I discuss how gender-based violence, while apparent during peacetime, becomes amplified during conflict, and how this violence physically inscribes the Ukrainian female body as “Other.” To conclude, I discuss how the lived experiences of Ukrainian women become embodied through fear, yet silenced through the ongoing nature of this war, and I pose several questions that aim at creating space for women to share their painful experiences as an act of liberation.
Keywords: gender-based violence; gender roles; Eastern Europe; Ukrainian women; war tactics